PENGEMBANGAN STRATEGI MANAGEMENT PROYEK KONSEP GREEN BUILDING PADA PEMBANGUNAN KOS-KOSAN 6 LANTAI STRUKTUR BAJA DI DAGO BANDUNG JAWA BARAT - Edison H. Manurung; Akhmad Faruq (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Green building is a development concept that pays attention to the efficiency of energy, water, materials, as well as the comfort and health of its residents. Its main goal is to minimize environmental impact and improve sustainability. Especially emphasized are several things, including the First energy and water efficiency, the Second indoor air quality, the Third reduction of emissions and waste, and the Fourth use of renewable resources. Lastly, climate adaptation and environmental conservation.